2013
DOI: 10.1098/rsta.2011.0587
|View full text |Cite
|
Sign up to set email alerts
|

Modelling interstellar physics and chemistry: implications for surface and solid-state processes

Abstract: We discuss several types of regions in the interstellar medium of the Milky Way and other galaxies in which the chemistry appears to be influenced or dominated by surface and solid-state processes occurring on or in interstellar dust grains. For some of these processes, for example, the formation of H 2 molecules, detailed experimental and theoretical approaches have provided excellent fundamental data for incorporation into astrochemical models. In other cases, there is an astrochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…In recent years, laboratory experiments and theoretical calculations have suggested that UV photon-induced surface and bulk processing of icy grain mantles containing water, carbon monoxide, methanol, and ammonia is one of the main mechanisms for the synthesis of "complex" organic molecules found in hot molecular cores and corinos, the regions within dark, dense molecular clouds warmed by one or more nearby protostars. [11][12][13] The source of UV light that initiates these chemical reactions is thought to be local because externally sourced UV radiation cannot penetrate these dark, dense molecular clouds. The UV photons are believed to form in these molecular clouds where cosmic rays with energies between 10 and 100 MeV ionize molecular hydrogen to generate secondary electrons, each with a mean energy around 30 eV.…”
Section: Faraday Discussionmentioning
confidence: 99%
“…In recent years, laboratory experiments and theoretical calculations have suggested that UV photon-induced surface and bulk processing of icy grain mantles containing water, carbon monoxide, methanol, and ammonia is one of the main mechanisms for the synthesis of "complex" organic molecules found in hot molecular cores and corinos, the regions within dark, dense molecular clouds warmed by one or more nearby protostars. [11][12][13] The source of UV light that initiates these chemical reactions is thought to be local because externally sourced UV radiation cannot penetrate these dark, dense molecular clouds. The UV photons are believed to form in these molecular clouds where cosmic rays with energies between 10 and 100 MeV ionize molecular hydrogen to generate secondary electrons, each with a mean energy around 30 eV.…”
Section: Faraday Discussionmentioning
confidence: 99%
“…Astrochemical observations of protoplanetary disks that surround distant stars along with space missions that targeted icy moons and interstellar bodies provide enough evidence on these huge chemical factories to suggest that complex organic chemistry is ubiquitous beyond our tiny planet . In such scenarios, the chemistry appears to be influenced or largely dominated by surface and solid‐state reactions (e.g., on dust grains), which are clearly different from processes that occur in gas‐rich atmospheres or wet environments . A plethora of neutral species and ions have been detected in the interstellar medium, which range from simple diatomic molecules to polyatomic carbon‐bearing species, such as glycolaldehyde, cyanamide, glycine, or low‐mass alcohols .…”
Section: Introductionmentioning
confidence: 99%
“…Investigating the properties of reactions that take place in naturally-occurring cold environments is necessary in order to accurately model their chemistry. [1][2][3][4][5][6][7][8][9][10] Even now, many of the reactions postulated to be of astrochemical importance are yet to be experimentally measured under cold conditions.…”
Section: Introductionmentioning
confidence: 99%